The history of Bhutan / (Acc: 5475) - Karma Phuntsho (India : Random House, 2013)
In 2008, Bhutan emerged as the world s youngest democracy and crowned the world s youngest monarch. Today, it continues to enchant the rest of the world with its policy of Gross National Happiness and has become a popular travel destination. But despite its growing popularity and the rising scholarly interest in the country, Bhutan remains one of the most poorly studied places on earth. Karma Phuntsho s The History of Bhutan combines both traditional perspectives and modern academic analysis and tells the full story of Bhutan for the first time in the English language. Primarily a historical account, it also includes substantive discussions of Bhutan s geography, culture and society to give readers an incisive introduction to the country.
Keywords: History --Bhutan